The structure of character: On the relationships between character strengths and virtues. Issue 1 (2nd January 2021) - Ruch, Willibald; Gander, Fabian; Wagner, Lisa; Giuliani, Fiorina
ABSTRACT: Character strengths are morally valued trait-like personality characteristics which contribute to fulfillments that comprise the good life, for oneself and for others. In two studies, we tested the assignment of the 24 character strengths of the VIA classification to the 6 virtues. In Study 1 ( N = 225), participants gave descriptions of situations where they applied their highest character strength in an excellent manner and rated each of these situations with respect to the six virtues. In Study 2 ( N = 146) participants judged the degree to which each character strength fulfills the six functions associated with the virtues. The results converged with the theoretical model for most of the 24 character strengths. Additionally, we consider both dichotomous and polytomous assignments of character strengths to virtues and compare the results with earlier findings and factor analyses of the VIA-IS. Further research using different approaches is suggested to proposealternative assignments of character strengths to virtues.